Peran Bakteri Endofit dalam Peningkatan Ketahanan Pangan Berbasis Pertanian Organik - Eka Satria Wibawa; Andi Ningrat (CV. Aksara Global Akademia, 2025)
Modern agriculture faces serious challenges such as climate change, soil degradation, and dependence on chemical fertilizers and pesticides, which negatively impact the environment and human health. To support sustainable food security, innovative and environmentally friendly solutions are required. One promising alternative is the use of endophytic bacteria as biological agents to enhance plant growth without relying on synthetic chemicals. This study aims to examine the role of endophytic bacteria in organic farming systems through a combination of laboratory tests and field experiments. The research stages include isolation and identification of endophytic bacteria from plant tissues, testing the ability of the bacteria to support plant growth in vitro, and applying it to organic farmland to evaluate resistance to pests and crop yields. The independent variable in the study is the type of endophytic bacteria, while the dependent variables include plant growth rates, pest resistance, and crop productivity. Data analysis was performed using descriptive statistics and ANOVA, followed by post-hoc tests to determine the effectiveness of the treatments. The results showed that treatments with endophytic bacteria, both singular and combined, significantly improved vegetative growth, reduced pest attacks, and increased crop yields compared to the control. The combination of bacterial isolates proved to have a stronger synergistic effect than single treatments. These findings demonstrate the potential of endophytic bacteria as natural biofertilizers and biopesticides to support environmentally friendly organic farming.